MODERN DIAGNOSTIC METHODS OF SYSTEMIC LUPUS ERYTHEMATOSUS (Лучшие интеллектуальные исследования, 2025)
Abstract: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease characterized by multisystem involvement and a wide range of clinical manifestations. Early and accurate diagnosis of SLE is crucial for effective management and prevention of complications. Over the years, significant advancements have been made in diagnostic techniques, including serological markers, imaging modalities, and genetic testing. This article explores the modern diagnostic methods for SLE, focusing on their accuracy, accessibility, and clinical relevance.